2013
DOI: 10.3748/wjg.v19.i45.8227
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmologic complications of antiviral therapy in hepatitis C treatment

Abstract: Antiviral therapy consisting of interferon-alpha and ribavirin for chronic hepatitis C infection is associated with multi-system side-effects. Ophthalmologic complications are common and can be classified into two groups: interferon-associated retinopathy and atypical adverse events. Interferon-associated retinopathy has been investigated by multiple observational studies that have found widely divergent results. The clinical importance of this complication is, consequently, controversial. This review examines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…8 In the literature, few published reports have estimated the relationship between viral hepatitis, liver cirrhosis, and the potential risk of uveitis. 1–7,15,16 Grob et al 1 demonstrated that 13% of patients with uveitis were sera positive for hepatitis B surface antigen in a study from Switzerland. A survey from England showed 2% of patients with various types of uveitis were sera hepatitis B surface antigen positive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 In the literature, few published reports have estimated the relationship between viral hepatitis, liver cirrhosis, and the potential risk of uveitis. 1–7,15,16 Grob et al 1 demonstrated that 13% of patients with uveitis were sera positive for hepatitis B surface antigen in a study from Switzerland. A survey from England showed 2% of patients with various types of uveitis were sera hepatitis B surface antigen positive.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Ocular manifestations related to treatment and nontreatment such as dry eye syndrome, Sjögren syndrome, xerophthalmia, Mooren ulcer, cystoid macular edema, ischemic retinopathy, ischemic optic neuropathy, uveitis, scleritis, and Vogt–Koyanagi–Harada disease with hepatitis B or C have been reported. 1–7,15,19,20 Nevertheless, the association between uveitis and viral hepatitis has not been extensively studied to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most frequent complications is an interferon-associated retinopathy [12], [13]. This retinopathy occurs in 30–60% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Conjunctivitis is the primary ocular side effect of ri bavirin. In addition, ribavirin increases the risk and severity of retinopathy when combined with IFN (81) . This potentiating effect of IFN can be ascribed to changes in the immune system in the balance between type 1 and 2 T-helper cells (82,83) .…”
Section: Ocular Changes Associated With Ifn and Ribavirin Treatmentmentioning
confidence: 99%